Filogenia molecular e diversificação das arraias de ferrão de água doce (Família Potamotrygonidae) na América do Sul - Ribeiro, Daniel Toffoli (Universidade Federal de São Carlos, 2013)
The network of South American rivers network has experienced deep changes during Late Miocene through Pleistocene, including major marine transgressions, Andean uplift driving drainage changes, and changes in eustatic level. After a marine transgression during Late Miocene in northwest South America, the ancestor of freshwater stingrays (Potamotrygonidae) adapted to the freshwater environment. Since then, the group has diversified while colonizing new drainage networks, given rise to new phenotypes and diet preferences. There are currently 24 species described, a number that will certainly rise once new species already known are described and new geographical regions are sampled. In the present work, I present a phylogeny for the Potamotrygonidae family based on molecular markers, with estimates of age and statistical tests of changes in rates of diversification while also testing for the occurrence of hybridization among some species of the family. The pattern of diversification in time and space was interpreted in light of major paleogeographical events that shaped drainage networks in South America during the Neogene, Mitochondrial and nuclear data corroborate the hypothesis of family origin in northwest South America around 25 Million years ago (MYA), after a major marine transgression, in a time when the Andes was not a topographic barrier between the Caribbean Sea and coastal regions. After those hydrographic basins were differentially colonized, whereas lineages that given rise to the genera Heliotrygon and Plesiotrygon possibly originated in the Pebas System, the lineage that gave rise to Potamotrygon probably was restricted to the region that is now the upper Negro river/Orinoco/Essequibo. After the inversion of the proto-Amazonas direction from East-West to West-East and reorganization of drainages, the Potamotrygon stingrays colonized both West portions of the Amazon Basin, previously occupied by Pebas megawetlands, and an Eastern portion, previously isolated by the Purus Arch. Contrary to the more accepted hypothesis, the estimated speciation ages suggest that this reorganization occurred around 3 MYA. Alternatively, the inversion of proto- Amazonas may have occurred earlier but the Negro river basin was kept isolated from the Amazon Basin at least as long to prevent stingrays dispersion. Following the reorganization of the drainages, a group of Potamotrygon named spotocellated underwent an increase in speciation rate – a radiation – as new regions were colonized. Upstream colonization of Crystalline Shields probably occurred in periods of higher eustatic level at the end of Pliocene, followed by vicariance after reduction of water levels.The Paraguai-lower Paraná basin was probably colonized at this same time, after headwater capture between Paraguai and Amazon Basins driven by foredeep formation. During the radiation, extensive hybridization took place among species of the spot-ocellated group.
Keywords: Genética Evolutiva; Neógeno; América do Sul; Paleogeografia; Radiação; Hibridação; Potamotrygonidae; Neogene; South America; Paleogeography; Radiation; Hybridization; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL